Marketing Communication Strategy of PT Tempo Inti Media Impresario in the field of Event Organizer (EO) in Indonesia - Alfianto, Mochamad Amboro (Budapest International Research and Critics University, 2021)
PT Tempo Inti Media Impresario is a member of Tempo Media Group, where the company runs a business in the event that the business is developing in Indonesia. But there is an interesting phenomenon here is the emergence of new EO from the major media in Indonesia such as Kompas, Media Indonesia, Tribune and others, here researchers want to reveal Marketing Communications Strategy of PT Tempo Impresario related to how PT Tempo Impresario faces business competition with competitors who have the same value. The purpose of this study is to see whether the marketing communication strategy of PT Tempo Inti Media Impresario is in line with reality in Lapanagan. The methodology used is qualitative in which the information gathering technique used is in-depth interviews aided by using SOSTAC analysis. And the results found are less maximum marketing communication strategy in the advertising and personal selling components in running the strategy that has been in the plan. The researcher suggested that PT Tempo Inti Media Impresario once again examined deeply related to the development of industry so that in planning can produce a plan that follows the development of MICE industry in Indonesia.